THE CONTRIBUTION OF THE TRAINING COURSE FOR MULTIPLIERS IN WORKSHOPS-CAREGIVING FOR THE CAREGIVER∕ RESCUE OF SELF-ESTEEM IN THE TRANSFORMATION OF THE PERCEPTION OF SELF-CARE BY PRIMARY CARE PROFESSIONALS - Carvalho Lima, Raquel; Gilvandra de Souza Dantas, Walkiria; Regina Alexandre Souza, Pâmela; Fernandes Filgueiras, Mateus; Beatriz de Andrade Silva, Maria; Corrêa Bezerra de Araújo, Renata; Carvalho Santana, Fabio; Claudino do Nascimento, Nathalia (Health and Society, 2023)
Objectives: To investigate how the course “Training of Multipliers in Workshops - Caring for the Caregiver∕ Regaining Self-Esteem” contributed to a new perception of self-care, experienced by professionals working in the PCU in the city of João Pessoa, in spite of situations of emotional fragility, triggered in the work environment. Method: The study used a qualitative approach, using as method for data collection a semi-structured questionnaire with questions about self-care practices used before and after the course. The research population included participants of the course in 2013 and the sample was composed of all who provided the necessary information, resulting in 36 participants. Results: It was observed through the answers, significant changes in everyday practices related to self-care, where 29 participants, equivalent to 81%, were influenced by the course. Conclusion: It was significantly observed that the course changed the understanding of self-care by developing its experiences with the participants.